Estudo do desgaste por erosão de ligas metálicas utilizadas em sistemas mecânicos de plantas siderúrgicas - Ewald, Heiter (2011)
The solid particle erosion is a serious and continuing problem in many industrial operations. Several mechanical systems are continuously exposed to environments where there are hard particles travelling at substancial speed. These particles impact and degrade the materials used there. This work aims to study three candidate materials for use in coif converters. The study was based initially on conditions presented by ASTM G 76-02 which governs the use of air jet impingement erosion rig - equipment used. These conditions are: speeds of 30 and 70 m/s and impact angle of 90°. To approach this study of actual conditions of coif converters, also conducted tests on the impact angle of 30°. The materials used were A36 steel, steel 15Mo3 and Inconel 625. The test results confirmed several concepts and behaviors already described in the literature on erosion and also presented an interesting variation in performance wear steel 15Mo3 with the variation of impact velocity. This behavior was attributed to the different mechanical energy density of the materials.